Down-regulated hsa_circ_0067934 facilitated the progression of gastric cancer by sponging hsa-mir-4705 to downgrade the expression of BMPR1B - He, Shen-Nan; Guan, Shi-Hua; Wu, Meng-Yao; Li, Wei; Xu, Meng-Dan; Tao, Min (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Gastric cancer is the third most lethal cancer worldwide. Finding a novel marker is essential to targeted therapy and the diagnosis of gastric cancer. As newly discovered markers, circRNAs have aroused widespread attention on a global scale. Our research aims to understand the role of circRNAs in gastric cancer and to explore the underlying pathogenesis. Methods: Raw expression data of circRNAs were obtained from the GEO database. Integrated bioinformatics analysis was used to screen differentially expressed circRNAs (DECs) by RobustRankAggreg package. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed to predict the functions of DECs. Then, the miRNAs and mRNAs at the downstream of DECs were predicted. Expression data of miRNAs and mRNAs were downloaded from The Cancer Genome Atlas (TCGA). The aberrantly expressed miRNAs and mRNAs were selected using the edgeR package. Results: Four datasets (GSE78092, GSE83521, GSE89143, and GSE93541) were downloaded from the GEO database. Among them, two DECs (hsa_circ_0007991 and hsa_circ_0067934) were screened. The functional analyses of DECs confirmed that they were cancer-related circRNAs. Furthermore, hsa-mir-4705 (miRNA) and BMPR1B (mRNA) at the downstream of hsa_circ_0067934 were found differentially expressed in gastric cancer by expression data from TCGA database. Conclusions: Our study discovered the critical roles of hsa_circ_0007991 and hsa_circ_0067934 in the development of gastric cancer, and they could be novel markers for targeted therapy and assist the diagnosis of early-stage gastric cancer. Moreover, we discovered that the hsa_circ_0067934/hsa-mir-4705/BMPR1B axis might be involved in the carcinogenesis of gastric cancer.